A Core Ontology of Know-How and Knowing-That for improving knowledge sharing and decision making in the digital age. Issue 2 (3rd April 2017) - Ghrab, Sahar; Saad, Ines; Kassel, Gilles; Gargouri, Faiez
Abstract: This paper proposes a Core Ontology of Know-How and Knowing-That (COOK). Know-How and Knowing-That are two types of knowledge according to the epistemological point of view. COOK is founded on work analysis in epistemology, philosophy of capacity/disposition and philosophy of action. This work allows to establish a conceptual analysis of Know-How and Knowing-That. Know-How is defined as the disposition to perform a type of action, whereas Knowing-That is defined as a belief state and concerns a description which can be factual or prescriptive. Taking into account the whole amount of data for an organisation, COOK enhances knowledge identification, decision-making and knowledge sharing among organisation or between different organisations geographically dispersed. Furthermore, COOK is used for the semantic refinement of knowledge evaluation criteria family. These criteria can be related to (i) functional point of view which aims to calculate the contribution degree of Know-How/Knowing-That to the organisation's objectives, (ii) generic point of view which determines the duration use of Know-How/Knowing-That in the organisation or (iii) ontological point of view which determines vulnerability criteria.